Penyusunan Laporan Keuangan dan Perancangan Aplikasi Keuangan Untuk Usaha Kecil Menengah Studi Kasus pada D’Haus Cake - Oliyan, Fitra; Santi, Elfitri; Rosalina, Eka (Jurusan Akuntansi Politeknik Negeri Padang, 2020)
This study aims to design accounting applications for the preparation of financial statements at D'Haus Cake's business. The approach used in this research is a case study. The design process begins with studying the transactions and reports that D'Haus Cake’s business needs in the form of purchase and sale transaction forms, and general journals. The required reports are in the form of all transaction journal records, ledgers, trial balances, profit and loss reports, and statements of financial position. After studying the system requirements, then proceed to the application development stage using Microsoft Access 2013 software. The next stage is to test the application to obtain adequate confidence in transaction processing by comparing the results of processing with manual calculations carried out. The implementation process is carried out by converting the initial data on the conversion date and making input transactions up to the company's operating date. After implementing and converting, the final stage is to carry out training for users and carry out a process of improvement and adjustment to the application based on the feedback received from users. The process of designing and implementing the application has been considered successful after the user states that the application has met all user needs and operates well.